Note—A Note on Economic Models for R&D Project Selection in the Presence of Project Interactions - Goldstein, Paula M.; Singer, Howard M. (Management Science, 1986)
In their paper, “Economic Models for R&D Project Selection in the Presence of Project Interactions,” Fox, Baker, and Bryant (Fox, G. E., N. R. Baker, J. L. Bryant. 1984. Economic models for R and D project selection in the presence of project interactions. Management Sci. 30 (July) 890–902.) proposed a model that included benefit interactions, called present value (PV) interactions, between R&D projects. Several computational errors in this paper invalidated the illustrative example which sought to demonstrate that ignoring the PV interactions could result in both nonoptimal project selections and resource allocations. However, a single correction yields an example that supports the authors' central premise. Furthermore, we believe that the model itself can prove useful in real applications.